1996
DOI: 10.1111/j.1945-5100.1996.tb02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Four lunar mare meteorites: Crystallization trends of pyroxenes and spinels

Abstract: Abstract— We studied crystallization trends of pyroxene and spinel in four Antarctic meteorites known to be derived from mare regions of the Moon: Y‐793169 and A‐881757 (YA meteorites) are unbrecciated igneous basalts, EET 87521 is a fragmental breccia, and Y‐793274 is a regolith breccia. All have relatively low bulkrock TiO2 content, and the YA meteorites are uncommonly ancient. Our electron probe microanalysis (EPMA) data indicate that the YA meteorites and the dominant mare components of Y‐793274 and EET 87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 21 publications
11
72
0
Order By: Relevance
“…They usually have a poikilitic texture or granulitic texture due to sub-solidus annealing (Heiken et al 1991). Arai et al (1996) found that Fe# [molar Fe/(Fe+Mg)] versus Ti# [molar Ti/(Ti+Cr)] of pyroxenes in lunar rocks displays three compositional trends. Pyroxenes from mare basalts show a strong correlation between Fe# and Ti#, reflecting local crystallization differentiation of interstitial melt.…”
Section: Affinities To Fan and Hms Suite Rocksmentioning
confidence: 99%
See 2 more Smart Citations
“…They usually have a poikilitic texture or granulitic texture due to sub-solidus annealing (Heiken et al 1991). Arai et al (1996) found that Fe# [molar Fe/(Fe+Mg)] versus Ti# [molar Ti/(Ti+Cr)] of pyroxenes in lunar rocks displays three compositional trends. Pyroxenes from mare basalts show a strong correlation between Fe# and Ti#, reflecting local crystallization differentiation of interstitial melt.…”
Section: Affinities To Fan and Hms Suite Rocksmentioning
confidence: 99%
“…These compositional trends may indicate a highlands origin or reflect thermal annealing histories. Arai et al (1996) argued that diffusion rates of Ti and Cr in pyroxenes are slower than that of Fe and Mg. Therefore, Fe and Mg are more readily homogenized than Ti and Cr.…”
Section: Affinities To Fan and Hms Suite Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigations (Arai et al 1996;Joy et al 2006) have proposed that pyroxenes from mare basalts commonly show a strong correlation between Fe# and Ti#. The correlation between Fe# and Ti# depends on chemical compositions of crystallizing basaltic magmas (Anand et al 2003).…”
Section: Fe-enrichment Of Mafic Lithic Clasts and Affinity To Lowti Bmentioning
confidence: 91%
“…The lunar meteorites contain information on the shock events that were common in the early lunar surface. Asuka-881757 lunar meteorite was discovered in Antarctica, and was described by some authors (3,4). This lunar meteorite is composed mainly of coarse aggregates of pyroxene, plagioclase (maskelynite), and ilmenite.…”
mentioning
confidence: 99%